SAT0135 COMPARISON OF THE EFFICACY AND SAFETY OF TWO BRIDGING SCHEDULES OF PREDNISOLONE IN EARLY ACTIVE RHEUMATOID ARTHRITIS (CORRA): A DOUBLE-BLIND, RANDOMISED, PLACEBO-CONTROLLED TRIAL. (2nd June 2020) - Krause, D.; Mai, A.; Timmesfeld, N.; Trampisch, U.; Klaassen-Mielke, R.; Rudolf, H.; Baraliakos, X.; Schmitz, E.; Fendler, C.; Klink, C.; Boeddeker, S.; Saracbasi, E.; et al.
Abstract : Background: Rheumatoid arthritis (RA) is a chronic inflammatory joint disease potentially leading to disability, impaired functioning, and premature death. Most treatment strategies include the early use of disease-modifying antirheumatic drugs (DMARDs) such as methotrexate (MTX) which is considered as an established 'anchor' therapy. Since it takes some weeks until MTX shows clinical efficacy, glucocorticoids (GC) are widely used for bridging. Objectives: The aim of the study "Comparison of the efficacy and safety of two starting dosages of prednisolone in early active RA" (CORRA) is to compare the efficacy and safety of two standard GC bridging schedules vs. placebo in addition to MTX, following a treat-to-target regimen, in early RA. Methods: CORRA is an investigator-initiated, randomised, multi-center, double-blind, placebo-controlled trial. Adult RA patients who were eligible for inclusion in the trial if they had a disease duration of less than 3 years and moderate or high disease activity were recruited in one hospital and 18 rheumatology practices in Germany. Patients were randomised (1:1:1) to receive 60 mg or 10 mg prednisolone (Pred) orally once daily (tapered down to 5 mg Pred within 8 weeks) or placebo. The duration of the intervention was 12 weeks, followed by an open observational phase for another 40 weeks. All patients were also treated with MTX (usually starting with 15mg/week followed by a treat-to target scheme). The primary efficacy endpoint was the progression of the radiographic joint damage after one year compared to baseline as determined by the van der Heijde modification of the Sharp score (SHS). Patients, physicians and readers of radiographs were unaware of the treatment assignments. For the comparison of the two GC groups, a non-inferiority margin of 1.3 points of the SHS was set. This trial was registered at ClinicalTrials.gov, number NCT02000336 . Results: Between February 2014 and February 2017, 395 patients were included in the trial, 381 of which had sufficient data also of follow-up visits. A total of 129 patients were assigned to the 60 mg Pred group, 124 to 10 mg Pred and 128 to the placebo group. At baseline, mean age was 58 years, 58% were female, 55% were rheumatoid factor and 52% ACPA positive. The mean number of swollen joints was 12.8 out of 28, mean ESR was 33.6 mm/h, mean CRP 2.2 mg/dL, mean DAS 28 6.0. Radiographic damage was 4.9 as measured by the SHS. In the 60 mg, 10 mg Pred group and in the placebo group, the DAS 28 was 2.6, 3.1, 4.5 at week 4 (p<0.001), 3.1, 2.8, 3.6 at week 12 (p<0.001), and 2.7, 2.6, 2.8 at week 52 (p=0.411), respectively. After 12 months the radiographic progression could be determined in 375 patients. In the 60 mg, 10 mg Pred group, and in the placebo group, the mean progression after 1 year was 1.0, 1.0, 1.1 for the total SHS and 0.5, 0.6, 0.7 for the erosion score of the SHS, respectively. Statistical analysis showed non-inferiority of the 10 mg Pred and of the placebo group in comparison to the 60 mg Pred group. Regarding safety issues, there were 10, 5, 6 serious adverse events and 31, 16, 20 adverse events in the MedDRA system organ class "infections and infestations" for the 60 mg Pred, 10 mg Pred, and the placebo group, respectively. Conclusion: The bridging schedule starting with 60 mg Pred reduced disease activity better than the 10 mg schedule or placebo only for a short time. The primary outcome structural damage was non-inferior in the 10 mg Pred and the placebo group in comparison to the 60 mg Pred group. Initial advantages of the higher dose may have been compromised by the long follow-up with the possible escalation of therapy due to the treat-to-target regimen. Disclosure of Interests: Dietmar Krause Grant/research support from: Pfizer and AbbVie (Abbott), Anna Mai: None declared, Nina Timmesfeld: None declared, Ulrike Trampisch: None declared, Renate Klaassen-Mielke: None declared, Henrik Rudolf: None declared, Xenofon Baraliakos Grant/research support from: Grant/research support from: AbbVie, BMS, Celgene, Chugai, Merck, Novartis, Pfizer, UCB and Werfen, Consultant of: AbbVie, BMS, Celgene, Chugai, Merck, Novartis, Pfizer, UCB and Werfen, Speakers bureau: AbbVie, BMS, Celgene, Chugai, Merck, Novartis, Pfizer, UCB and Werfen, Elmar Schmitz: None declared, Claas Fendler: None declared, Claudia Klink: None declared, Stephanie Boeddeker: None declared, Ertan Saracbasi: None declared, Jochen Christoph: None declared, Manfred Igelmann: None declared, Hans Juergen Menne: None declared, Albert Schmid: None declared, Hans J Trampisch: None declared, Juergen Braun Grant/research support from: Abbvie (Abbott), Amgen, BMS, Boehringer, Celgene, Celltrion, Centocor, Chugai, Eli Lilly and Company, Medac, MSD (Schering Plough), Mundipharma, Novartis, Pfizer (Wyeth), Roche, Sanofi- Aventis, and UCB Pharma, Consultant of: Abbvie (Abbott), Amgen, BMS, Boehringer, Celgene, Celltrion, Centocor, Chugai, EBEWE Pharma, Eli Lilly and Company, Medac, MSD (Schering-Plough), Mundipharma, Novartis, Pfizer (Wyeth), Roche, Sanofi-Aventis, and UCB Pharma, Speakers bureau: Abbvie (Abbott), Amgen, BMS, Boehringer, Celgene, Celltrion, Centocor, Chugai, EBEWE Pharma, Eli Lilly and Company, Medac, MSD (Schering-Plough), Mundipharma, Novartis, Pfizer (Wyeth), Roche, Sanofi-Aventis, and UCB Pharma